A Transparent, Self‐Healing, Highly Stretchable Ionic Conductor. Issue 10 (23rd December 2016) - Cao, Yue; Morrissey, Timothy G.; Acome, Eric; Allec, Sarah I.; Wong, Bryan M.; Keplinger, Christoph; Wang, Chao
Abstract : Self‐healing materials can repair damage caused by mechanical wear, thereby extending lifetime of devices. A transparent, self‐healing, highly stretchable ionic conductor is presented that autonomously heals after experiencing severe mechanical damage. The design of this self‐healing polymer uses ion–dipole interactions as the dynamic motif. The unique properties of this material when used to electrically activate transparent artificial muscles are demonstrated.